2010
DOI: 10.1007/s12539-010-0097-7
|View full text |Cite
|
Sign up to set email alerts
|

Na+, K+ and Tl+ hydration from QM/MM computations and MD simulations with a polarizable force field

Abstract: The hydration of three different monovalent cations was studied with a number of theoretical approaches ranging from classical MD simulations to MD simulations with a polarizable force field and finally to QM/MM MD. A particular emphasis was put on the development of a novel polarizable potential function for studies of Tl(+) hydration enabling the ability to reproduce key features observed in QM/MM simulations. We extended the CHARMM-deMon interface developed previously to studies of ion hydration with QM/MM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…For example, the Car–Parrinello dynamics has been applied to examine the hydration of Cl − , Li + , and Na + ions. Other examples are the QM/MM dynamics simulations of the Cl − , Li + , Na + , and NH4+ . Those theoretical investigations have contributed significantly to our understanding of those hydrated ions.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the Car–Parrinello dynamics has been applied to examine the hydration of Cl − , Li + , and Na + ions. Other examples are the QM/MM dynamics simulations of the Cl − , Li + , Na + , and NH4+ . Those theoretical investigations have contributed significantly to our understanding of those hydrated ions.…”
Section: Methodsmentioning
confidence: 99%
“…33 In addition to studies of ions with crown molecules, many studies have used QM calculations to investigate the interaction between ions with water clusters. [55][56][57][58] It was shown that the structure of such clusters is a delicate competition between ionwater and water-water interactions. 59 The hypothesis that water molecules interact with the hydraphile and assist in the action of the ion channel properties will be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, combined quantum mechanics/molecular mechanics (QM/MM) methods have become useful tools, where the system is divided into a small QM region and a large MM region , but suffers limitations in meaningful separation of QM and MM regions and also lacks the ability to extend to greater system sizes and time scales . The application of QM and QM/MM methodologies for ion channel simulations has been very limited to date, instead focusing on models of ion solvation , or specific interactions . It is for this reason that purely classical modeling of protein function still provides the best route to sampling protein structure–function relationships, incorporating realistic descriptions of protein interactions with lipids, solvent, ions, and ligands, while covering much of the necessary length and time-scales for function, and enabling calculations of thermodynamic and kinetic measurables …”
Section: Molecular Mechanical Models Of Membrane Ion Channelsmentioning
confidence: 99%